Prevention of common mental disorders among women in the perinatal period: a critical mixed-methods review and meta-analysis - Ahmed Waqas; Syeda Wajeeha Zafar; Hafsa Meraj; Mahjabeen Tariq; Sadiq Naveed; Batool Fatima; Neerja Chowdhary; Tarun Dua; Atif Rahman (Cambridge Prisms: Global Mental Health, 2022)
Perinatal depression and anxiety account for a high burden of perinatal morbidity and poor psychosocial functioning. There is a growing interest among mental health professionals, to devise interventions to prevent this condition. This review synthesizes evidence for the effectiveness of psychological and psychosocial interventions aimed at the prevention of perinatal depression and anxiety. We also explore qualitative evidence to understand the acceptability and feasibility of these interventions. Using a mixed-methods approach, data from a total of 21 studies were collated to inform the evidence for preventive interventions for perinatal depression and anxiety. Based on their theoretical orientations, these interventions were described by authors as cognitive-behavioral (n = 7); psychoeducational (n = 6); mindfulness (n = 2); and interpersonal psychotherapy (n = 2). These also included psychosocial approaches such as social support (n = 1) and multicomponent interventions (n = 3). For depressive symptoms, these interventions yielded moderate to strong effect sizes in favor of the intervention group [standardized mean difference (SMD) = −0.59; 95% confidence interval (CI) −0.95 to −0.23]. For anxiety symptoms, a strong effect size was estimated in favor of the intervention group (SMD = −1.43, 95% CI −2.22 to −0.65). Preventive interventions significantly reduce the severity of perinatal depressive and anxiety symptoms. These interventions are also acceptable and feasible in many settings.